Effect of different exercise interventions on metabolic syndrome risk factors in postmenopausal women: a network meta-analysis - Zhang, Tongyan; Kabachkova, Anastasiia V.; Deng, Zifu; Liang, Yishu; Li, Meng; Yuan, Wenxue (Frontiers in Physiology, 2025)
ObjectivesThe objective of this study was to compare and rank the effectiveness of various exercise interventions on metabolic syndrome (MetS) risk factors in postmenopausal women.MethodsA systematic search was conducted in PubMed, Cochrane, Embase, and Web of Science databases. Randomized controlled trials investigating exercise effects on MetS risk factors in postmenopausal women were included. Two reviewers screened articles, extracted data, and assessed risk of bias and strength of evidence. Analysis was performed by RStudio and Stata 16.0.ResultsThis study encompassed 142 RCTs with 7,967 women. The results of the network meta-analysis indicated that combined training (CT) had the greatest effect on body weight (surface under the cumulative ranking [SUCRA] = 0.897), body mass index (SUCRA = 0.923) and triglyceride levels (SUCRA = 0.783); aerobic exercise (AE) had the most significant effect on body fat percentage (SUCRA = 0.856), low-density lipoprotein cholesterol (SUCRA = 0.765), and high-density lipoprotein cholesterol levels (SUCRA = 0.814); resistance training (RT) had the greatest effect on waist circumference (SUCRA = 0.834), glucose (SUCRA = 0.929),and total cholesterol levels (SUCRA = 0.776); mind-body exercise (MBE) had the most significant effect on diastolic blood pressure (SUCRA = 0.969), systolic blood pressure (SUCRA = 0.921), and adiponectin levels (SUCRA = 0.808).ConclusionAE, CT, RT, and MBE demonstrated varying degrees of effectiveness in improving different MetS risk factors in postmenopausal women. Selecting appropriate exercise modalities based on individual metabolic risk profiles and health goals is important to achieve optimal intervention outcomes. These findings provide valuable guidance for clinical practice. However, considering the limitations such as the low quality of evidence and high risk of bias in the included studies, the conclusions should be interpreted with caution.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023456584, identifier CRD42023456584.